Rhizospheric Microflora Of Citrus In Vidarbha Region Of Maharashtra (Journal of Plant Disease Sciences, 2022)
The soil samples collected from citrus rhizosphere of different orchards and nurseries were processed in the laboratory and Phytophthora parasitica was isolated by leaf bait technique, soil spreading and tissue isolation method on selective medium (PARPH). Out of fourty nine samples collected from three different locations from citrus orchards and nurseries. Pseudomonas fluorescens was isolated from twenty six soil samples on King’s B medium and Trichoderma was isolated from twenty five samples on Trichoderma selective medium by serial dilution method. Rhizospheric population of fluorescent Pseudomonas varied from 31 x 105 to 59 x 105 and rhizospheric population of Trichoderma varied from 17.67 x 104 to 42 x 104. Out of fourty nine soil samples thirty four samples were found associated with Phytophthora in the range of 15.89-35.25 propagules/ g soil. Pathogenicity was tested on detached leaves of Citrus jambhiri in Petri plate moisture chamber. The pathogen produced water soaked chocolet/ brownish lesions in the leaf lamina within 7 days after inoculation of fungus on host leaves.
Keywords: Phytophthora parasitica; Pseudomonas Trichoderma; Rhizosphere